The effect of supply chain management challenges on research and development projects using Fuzzy DEMATEL and TOPSIS approach - Forozandeh, Mohammad (Annals of Management and Organization Research, 2021)
Purpose: This paper aimed to identify, classify and prioritize supply chain management challenges for research-development projects in the R&D organization.Research Methodology: Based on previous literature and interview with related experts, the initial challenges of SCM for research-development projects in Iran organization were extracted. Thereafter, the identified challenges were finalized, classified, and prioritized. For this purpose, a semi-interview and questionnaire were designed, applied, and then analyzed using some statistical methods. Validation of the results was done through several interviews. Finally, the necessary modifications were made to the factors of environmental sustainability associated with the COVID-19 crisis. Results: In this study, the challenges of SCM for research-development projects in Iran organization were divided into six categories: cultural, motivational, contextual, process, infrastructural, and capabilities. Thereafter, suggested solutions were presented which describe how the challenges of SCM in research-development projects may be removed progressively. Limitations: This research is only described in project-based organizations. The study was limited to construction projects in different cities of Iran.Contribution: The prioritized challenges of SCM are a guideline for managers or decision-makers of R&D projects which will enable them, resolve challenges or improve on decision making. It also serves as a useful base for researchers to expand further research concerning the challenges of SCM in other research-development organizations. This study may present high value for researchers in the SCM field for research-development projects. Also, this study presents several solutions for the improvement of challenges considering the level of their importance to SCM.